The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/buildings12050586
|View full text |Cite
|
Sign up to set email alerts
|

Carbonation and Corrosion Problems in Reinforced Concrete Structures

Abstract: Reinforced concrete (RC) has been commonly used as a construction material for decades due to its high compressive strength and moderate tensile strength. However, these two properties of RC are frequently hampered by degradation. The main degradation processes in RC structures are carbonation and the corrosion of rebars. The scientific community is divided regarding the process by which carbonation causes structural damage. Some researchers suggest that carbonation weakens a structure and makes it prone to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 91 publications
0
10
0
Order By: Relevance
“…In general, mortars with a higher sand content (1:2) showed reduced resistance to carbonation and water absorption, which was consistent with the previous research by Huang et al [ 157 ], which showed that CO 2 gas penetrates the concrete surface through the sand-cement gap [ 157 ]. This means that increasing the volume of sand in concrete also increases CO 2 penetration [ 158 ]. Duan et al [ 156 ] noted an improvement in carbonation resistance by 77%, 62%, and 42% for fluidized bed fly ash geopolymer paste samples containing 1%, 3%, and 5% NT, respectively, after 180 days of exposure.…”
Section: Results Of Mechanical Properties Of Modified Cement Mortarsmentioning
confidence: 99%
“…In general, mortars with a higher sand content (1:2) showed reduced resistance to carbonation and water absorption, which was consistent with the previous research by Huang et al [ 157 ], which showed that CO 2 gas penetrates the concrete surface through the sand-cement gap [ 157 ]. This means that increasing the volume of sand in concrete also increases CO 2 penetration [ 158 ]. Duan et al [ 156 ] noted an improvement in carbonation resistance by 77%, 62%, and 42% for fluidized bed fly ash geopolymer paste samples containing 1%, 3%, and 5% NT, respectively, after 180 days of exposure.…”
Section: Results Of Mechanical Properties Of Modified Cement Mortarsmentioning
confidence: 99%
“…In this expression, j 1 (a) is the value of the mass flow of chloride ions passing through the plane situated at "a" distance x = a; ρ 1 1 , ρ 1 2 , and ρ 1 n are the averaged mass densities of ion Cl − at the midpoints of consecutive intervals (0, g), (g, 2g), . .…”
Section: Migration Studies and Determination Of Diffusion Coefficient...mentioning
confidence: 99%
“…Depending on their location and function, building structures are exposed to many harmful factors. The most common causes of reinforcement corrosion and concrete damage are carbonation and chloride penetration [ 1 ]. The faster the carbon dioxide or chlorides penetrate the concrete, the faster the passive layer on the rebar is destroyed and the corrosion process begins [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The number and size of the cracks increase the permeability of concrete, which is one of the critical parameters reducing its durability [12]. Chloride ions, carbon dioxide and oxygen dissolved in water lead to corrosion on the rebar, resulting in potential structural failures [13][14][15]. Therefore, many traditional maintenance and fixing methods have been implemented to avoid this type of degradation.…”
Section: Introductionmentioning
confidence: 99%